1895 Fla. Laws 14 - (:unkn) unknown (My University, 1895)
No merchant, store-keeper or dealer shall keep for sale or sell pistols, Springfield rifles, repeating rifles, bowie knives or dirk knives, without first paying a license tax of ten dollars; Provided, Said pistols, Springfield rifles, repeating rifles, bowie knives or dirk knives, shall not be sold to minors.
Keywords: TAX - DEALERS; TRANSFER - MINORS